THE EFFECTIVITY OF WARM COMPRESSES AND MASSAGE EFFLEURAGE TO DISMENOREA INTENSITY IN PESANTREN AR RISALAH PADANG - Viki yusri (Stikes Syedza Saintika Padang, 2018)
Dysmenorrhea is pain that is felt during menstruation. More than 50% of women in each country experience menstruation with Dysmenorrhea. Effleurage and warm compress techniques are currently widely used to reduce the intensity of dysmenorrhea. Aiming at research to determine the effectiveness of warm compresses, effleurage massage and combination of intensity of Dysmenorrhea , the samples used were 10 people for each treatment group, with purposive sampling technique. This study uses experimental research design, design of one group pretest-posttest. The dysmenorrhea intensity measuring instrument was performed using the Manskoski Pain Scale. Data analysis was performed using paired sample t test and one way anova test. The results of statistical tests showed that warm compresses, massage effleurage and combination proved to be effective in reducing the intensity of Dysmenorrhea (p <0.05). In conclusion, warm compresses and massage effleurage were relatively the same in reducing the intensity of dysmenorrhea (p-value 0.353), while the combination method was more effective in reducing the intensity of dysmenorrhea (p-value 0.047). It is recommended if possible to use a combination method to reduce the intensity of dysmenorrheal Keywords: Effleurage and warm compresses, intensity of dysmenorrh